Proline and reactive oxygen/nitrogen species metabolism is involved in the tolerant response of the invasive plant species Ailanthus altissima to drought and salinity - Filippou, Panagiota S.; Bouchagier, Pavlos; Skotti, Effie; Fotopoulos, Vasileios (My University, 2014)
Ailanthus altissima (Miller) Swingle (family Simaroubaceae), commonly known as the ‘Tree of Heaven’, grows aggressively in harsh environments where it invades abandoned fields or cracked city sidewalks. The present study deals with the adaptation of defence mechanisms of A. altissima seedlings subjected to two of the most important abiotic stress factors worldwide, drought and salinity. Salinity-stressed A. altissima seedlings were obtained by watering the plants with two different NaCl concentration solutions (150 and 300 mM) for 48 h, while drought-stressed plants were obtained after withholding watering for 14 d. Physiological parameters, reactive oxygen/nitrogen species and malondialdehyde content measurements in stressed plants indicated the abiotic stress factor-specific regulation of its defence response. Moreover, the content of the osmoprotective molecule proline was also affected by both stresses in parallel to the oxidative/nitrosative markers. Nitrate reductase enzymatic activity and protein content involved in nitric oxide biosynthesis, Δ1-pyrroline-5-carboxylate synthetase enzymatic activity involved in proline biosynthesis, as well as the activity of H2O2-generating and scavenging enzymes (superoxide dismutase and catalase, respectively), provided further biochemical support for the specific abiotic stress tolerance mechanism of this invasive plant species.
Keywords: Abiotic stress; Reactive oxygen species; Reactive nitrogen species; Proline; Nitrate reductase; Ailanthus altissima